Mechanical and Chemical Properties at High Temperature of M-25Cr-based Alloys Containing Hafnium Carbides (M=Co, Ni or Fe): Creep Behavior and Oxidation at 1200°C (Journal of Material Science and Technology Research, 2014)
This study concerns three alloys based on cobalt, nickel or iron, all containing chromium (25 wt.%), carbon and hafnium. The contents in the two last elements were chosen high enough to promote the formation of HfC carbides. All alloys were elaborated by casting and their microstructures preliminarily characterized. They were selected to be tested in three-points flexural creep at 1200°C under 20 MPa in inert atmosphere. All alloys contain hafnium carbides, together with chromium carbides in some cases. The HfC carbides are generally of two types: script-like eutectic and blocky pre-eutectic. The creep deformation is fast for the nickel-based and iron-based alloys, especially for the later one. In contrast the HfC-containing cobalt-based alloy behaves much better. It displays a creep resistance at 1200°C significantly higher than another cobalt-based alloy strengthened by chromium carbides added to the study for comparison. All alloys were also briefly tested in oxidation by air at 1200°C. The creep behaviors of the cobalt-based and iron-based alloys are not good and significantly worse than the nickel-based alloy’s one. The oxidation resistance of the HfC-strengthened cobalt-based alloy must be improved to take benefit of its superior creep strength.